Niosomes loaded with diclofenac for transdermal administration: Physico-chemical characterization, ex vivo and in vivo skin permeation studies - Yen Thi Hai Tran, Giang Ngoc Tran, Anh Lan Hoang, Giang Thi Thu Vu (Journal of Applied Pharmaceutical Science, 2020)
The objectives of this study were to prepare and characterize niosomes loaded with diclofenac (DiC), to evaluate skin permeation of DiC niosomes by ex vivo and in vivo studies. DiC niosomes were prepared by ethanol injection method using nonionic surfactant Span 80 and cholesterol in different molar ratios. The vesicle size and polydispersity index (PDI) of DiC niosomes were determined by dynamic light scattering method. Niosomal vesicles were also investigated by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and field emission scanning electron microscopy studies. The transdermal permeation of niosomal hydrogel was assessed in both ex vivo and in vivo studies on rats. The results showed that DiC niosomes were spherical particles in shape with the average vesicle size of less than 100 d.nm; PDI was smaller than 0.2. Results of DSC and FTIR showed that the drug no longer remained in its crystalline form after niosomes had been formed; it might disperse in the bilayer of niosomes. The data of ex vivo and in vivo experiments suggested that DiC niosomal hydrogel not only improved the amount and rate transport of DiC through the skin but also increased drug concentration in the muscle in comparison to the commercial drug.
Keywords: Niosomes, diclofenac, skin permeation, drug concentration in muscle, ex vivo study, in vivo study.